Let's solve the equation step by step.
Starting with the equation:
\[ 3(x - 5) + 2x = 0 \]
-
Distribute \(3\) to \(x - 5\): \[ 3x - 15 + 2x = 0 \]
Now we can fill in the first blank as \(-15\):
\[ 3x + \underline{-15} + 2x = 0 \]
-
Combine like terms: \[ 3x + 2x - 15 = 0 \] \[ 5x - 15 = 0 \]
Now we can fill in the second blank as \(15\):
\[ 5x = \underline{15} \]
-
Solve for \(x\): \[ 5x = 15 \] \[ x = \frac{15}{5} \] \[ x = 3 \]
Now we can fill in the last blank as \(3\):
\[ x = \underline{3} \]
Putting it all together, we have:
- The first blank is \(-15\)
- The second blank is \(15\)
- The third blank is \(3\)
So, the completed steps are:
- \(3x + \underline{-15} + 2x = 0\)
- \(5x = \underline{15}\)
- \(x = \underline{3}\)